Attitudinal Evaluation in Chinese University Students' English Writing A Contrastive Perspective - Liu, Xinghua (Corpora and Intercultural Studies,, 2018)
This book offers up-to-date insights into the long-standing controversy of whether or not Chinese learners of English adequately express their attitudes in written English. It compares four writing datasets from three groups of student writers (e.g., English-speaking students' English texts, Chinese-speaking students' Chinese texts, and both English and Chinese texts produced by the same group of Chinese-speaking students majoring in English), and applies the appraisal framework, an analytical tool developed in the field of Systemic Functional Linguistics. The book provides a nuanced view of the deployment of attitudinal patterns and the linguistic resources used for attitudinal evaluation in Chinese students' English writing. Accordingly, it offers a valuable resource for all those interested in second language writing, contrastive rhetoric, second language acquisition and systemic functional linguistics. .